Microsatellite primers for the fungi Rhizopogon kretzerae and R. salebrosus (Rhizopogonaceae) from 454 shotgun pyrosequencing1. (10th July 2014) - Grubisha, Lisa C.; Brewer, Jessica D.; Dowie, Nicholas J.; Miller, Steven L.; Trowbridge, Steven M.; Klooster, Matthew R.
Abstract : Premise of the study: Rhizopogon kretzerae and R. salebrosus (Rhizopogonaceae) are ectomycorrhizal fungi symbiotic with pines and the mycoheterotrophic plant Pterospora andromedea (Ericaceae). Microsatellite loci will allow population genetic study of fungal hosts to P. andromedea . Methods and Results: Shotgun pyrosequencing of R. kretzerae DNA resulted in primer development of 23 perfect microsatellite loci and screened across two populations each for R. kretzerae and R. salebrosus . Twelve loci were polymorphic in R. kretzerae populations, and 11 loci cross‐amplified in R. salebrosus populations. For R. kretzerae and R. salebrosus, number of alleles was one to eight and one to nine, respectively, and observed heterozygosity ranged from 0.00–0.57 and 0.00–0.70, respectively. Conclusions: These are the first microsatellite loci developed for any species within Rhizopogon subgenus Amylopogon . These microsatellite loci will be used in conservation genetic studies of rare to endangered eastern populations and to compare plant and fungal population genetic structure at different hierarchical levels.